Analisis Kriteria Penyusunan Sasaran Kerja Widyaiswara - Safriati Razali (Jurnal Transformasi Administrasi, 2017)
After the Government Regulation Number 46 Year 2011 on Public Servant’s Work Appraisal has been imposed, every public servant is demanded to set Job Target of Public Servants (SKP). As public servants, facilitators must also arrange job target in SKP. In arranging it, facilitators are obliged to refer to the Regulation of Ministry of State Apparatus Empowerment and Bureaucracy Reform (Permenpan and RB) Number 22 Year 2014 on Non-Managerial Position of Facilitator and Their Credit Score. This study aimed to investigate whether or not the arrangement of facilitators’ SKP has met two criteria required by the Permenpan and RB. This is a qualitative study, hence the data obtained from the field was deeply analyzed with descriptive method. The data were the SKP documents of some facilitators of Human Resources Development Agency of The Aceh Province. The findings depicted that almost all the facilitators did not arrange the SKP based on two criteria set by the Permenpan and RB. The unavailability of the criteria will cause the suspension of the facilitators’ grade or position promotion. The study suggested some alternative recommendations as the follow-up activities which will further discuss in the paper. This study outlines main and ancillary activities of facilitators, annual minimum credit score, and sub elements of mandatory activities which must be annualy actualized by facilitators according to the needs of their grade and position.